Kesalahan dan kebolehpercayaan alat ukur orientasi pembelajaran matematik (OPM) - Veloo, Arsaythamby; Awang Hashim, Rosna (Universiti Utara Malaysia, 2009)
Purpose - The Study Orientation Questionnaire in Mathematics (SOM)(Maree, Claassen, & Prinsloo, 1997) was used to measure individual behaviour based on five factors: study attitude, anxiety, study habits, problem-solving, and study milieu with specific reference to Mathematics. The study aimed to determine the validity and reliability, scale, and the interrelationship among the factors using the revised Study Orientation Questionnaire in Mathematics (SOM). The present study used SOM (76 items) with 17 additional items to assess the aff ective att ributes among secondary school students. Design/Methodology/Approach - A total of 195 Form Four students, 86(44%) boys and 109 (56%) girls, were selected from a school in Kedah. Back translation method was used to translate the 93 items in SOM; SPSS version 12 was used to analyse the construct validity by Chi-Square test (Bartlett ’s Test of Sphericity) and Kaiser-Meyer-Olkin (KMO), and the internal consistency reliability of the instrument (Cronbach’s alpha). WINSTEP version 3.48 was used to analyse the LIKERT scale to determine required patt erns of responses. Findings - Findings indicated that all fi ve factors were reliable with Cronbach’s Alpha of more than 0.70. All factors were related and thus represent a valid measure of SOM. Using step measures at interaction procedures, the initial five-likert-scaling (12345) was reduced to four (12245). The findings suggested that the third choice (not sure) was embedded under the second choice (disagree) indicating similar response pattern. Originality/Value - The study has successfully revised and validated the final SOM instrument with 72 items. SOM fulfills psychometric criteria such as validity, realiability, scale, and the interrelationship among five factors which asses stduents’ affective factors in learning Mathematics. Thus, the instrument can be used by teachers, counselors, and even principals to access OPM in understanding students’ study orientation problem in learning Mathematics.